Waste water quality assessment and its improvement through cost effective methodology for reuse - Ludri, Ashutosh (Indian Journal of Animal Nutrition, 2018)
Coagulation, adsorption and disinfection methods were used for purification of wastewater from effluent treatment plant (ETP) of NDRI, Karnal, India. Alum (1 g/L), charcoal (0.5 g/L) and chlorine (1%) for waste water treatment as effective dosages. The alkalinity, total hardness, total dissolved solids (TDS) and biochemical oxygen demand (BOD) reduced significantly and were, 146.4 mg/L, 125 mg/L as CaCO3, 480 mg/L and 0.88 mg/L (3 days at 27Â°C) respectively after treatment. The different physico-chemical properties (colour, odour, pH, alkalinity, hardness, TDS, BOD, nitrates and chlorides) of treated water samples were well within the permissible limits of different water standards. Â